2016
DOI: 10.1002/ijc.30278
|View full text |Cite
|
Sign up to set email alerts
|

D‐dopachrome tautomerase is over‐expressed in pancreatic ductal adenocarcinoma and acts cooperatively with macrophage migration inhibitory factor to promote cancer growth

Abstract: Previous studies have established the important role of MIF in the development of pancreatic ductal adenocarcinoma (PDAC) for both therapeutic and diagnostic perspectives, but little is known about the expression and function of D-dopachrome tautomerase (DDT), a functional homolog of MIF, in PDAC. In the present study, we demonstrated that DDT was over-expressed in PDAC tissues in a pattern correlated with MIF. In the pancreatic cancer cell lines, PANC-1, BXPC-3 and ASPC-1, both DDT and MIF were expressed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
(106 reference statements)
2
33
0
Order By: Relevance
“…The identification of molecules that are involved in PDAC tumor progression and aggressiveness may elucidate novel targets for PDAC treatment. Previous studies have suggested that MIF, a pro-inflammatory cytokine, facilitates cancer progression, associating inflammation with pancreatic cancer progression ( 12 14 , 23 ). Emerging research has explored the biological effects of MIF in PDAC ( 11 14 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of molecules that are involved in PDAC tumor progression and aggressiveness may elucidate novel targets for PDAC treatment. Previous studies have suggested that MIF, a pro-inflammatory cytokine, facilitates cancer progression, associating inflammation with pancreatic cancer progression ( 12 14 , 23 ). Emerging research has explored the biological effects of MIF in PDAC ( 11 14 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from different groups have identified an increased expression level and tumor-promoting functions of MIF in PDAC ( 11 14 ). MIF knockdown inhibits ERK1/2 and AKT phosphorylation, and upregulates p53 expression, in turn leading to cell cycle arrest and apoptosis in pancreatic cancer cells ( 11 , 12 ). Recently, Yang et al ( 13 ) reported a novel signaling pathway whereby MIF upregulates miR-301b, which subsequently targets nuclear receptor subfamily 3 group C member 2.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies on the role of DDT in cancer. It has been shown that the knockdown of DDT and MIF in the pancreatic cell line, PANC-1, correlated with reduced activation of ERK1/2 and AKT, augmented p53 expression, and inhibited tumor growth in vitro and in vivo [15,69]. The DDT interaction with CD74 stimulates the expression of VEGF and CXCL8 and counteracts the 5' AMP-activated protein kinase (AMPK) activation in human non-small cell lung carcinoma [70,71].…”
Section: Ddt (Mif2) and Cancermentioning
confidence: 99%
“…Interestingly, in contrast to the ability of MIF and DDT to activate AMPK in non-transformed cells, they cooperatively inhibited the activation of AMPK in LKB1 mutant human non-small cell lung cancer (NSCLC) cell lines [71]. Furthermore, treatment with the dual inhibitor of MIF and DDT, 4-iodo-6-phenylpyrimidine (4-IPP), decreased in vitro proliferation and in vivo tumor growth in a mouse xenograft model [69]. Moreover, in the melanoma cancer cell line B16F10, treatment with small interfering RNAs (siRNA)/DDT suppressed cell proliferation and stimulated apoptosis, and in a xenograft model treatment with anti-DDT antibodies reduced tumor growth [72].…”
Section: Ddt (Mif2) and Cancermentioning
confidence: 99%
“…Interestingly, concurrent knockdown of both D-DT and MIF resulted in enhanced inhibition of ERK1/2 and AKT and cell proliferation as compared to single MIF or D-DT shRNA treatment. Also, treatment of PANC-1 cells with the dual covalent tautomerase inhibitor of both MIF and DDT, 4-iodo-6-phenylpyrimidine (4-IPP), reduced proliferation and colony formation in vitro and tumor growth in the mouse xenograft model [ 48 ]. This is in line with data on the squamous carcinoma cell line, SCCVII [ 29 ], and on the A549 lung adenocarcinoma cells [ 49 ], where 4-IPP treatment reduced proliferation and invasiveness.…”
Section: D-dt (Mif-2) and Cancermentioning
confidence: 99%